Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.